Evaluation of Housing Project Business Feasibility Calculations from a Financial Perspective - Firdaus, Muhammad Avri; Frensidy, Budi (Dinasti International Journal of Education Management and Social Science, 2025)
This study evaluates the limitations of Return on Investment (ROI) as PT XYZ’s primary project assessment tool and contrasts it with the Discounted Cash Flow (DCF) and Net Present Value (NPV) approaches. Analysis of three projects reveals that ROI fails to account for the time value of money and tends to produce overly optimistic evaluations. Major deviations stem from cost overruns in operational, legal, and construction components, as well as oversimplified cash-flow assumptions. Qualitative findings confirm that reliance on ROI is driven by time pressure and limited expertise in DCF modeling. The simulation of Project D demonstrates that a conservative DCF framework provides a more accurate assessment and exposes hidden risks. This study recommends using ROI only as an initial screening tool, with final investment decisions based on NPV supplemented by scenario analysis.